Money Rates: Revision of the Money Curve of the Monthly Index Chart - Hubbard, Joseph B. (The Review of Economics and Statistics, 1931)
SINCE publication of the monthly index chart was begun in I919, two important revisions of the money curve (C) have been made. In its original form, the curve was based on rates for two grades of commercial paper, adjusted for seasonal variation on the basis of indexes computed for the interval I890-9I6, with a horizontal normal (at 4.645 per cent).' Beginning with January I922, the seasonal correction was reduced so that allowance was made for only onehalf the pre-war seasonal variation, and in May I923, the first important revision was made, the entire curve being recalculated back to January